PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERBANKAN JAKARTA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Widhah, Afifah; Addin, Syahrial (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
The banking sector is a funding sector that plays a major role in the economy. In addition, the banking sector is great demand by investors and many are listed on the Indonesia stock exchange. Therefore, company management tends to carry out a strategy in the form of earnings management in order to keep its profit fluctuations looking stable. This study aims to examine the effect of profitability and liquidity on firm value. The independent variables in the study are profitability and liquidity, while the dependent variable is firm value. This research uses quantitative research. This study used a sample of 8 banks listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The sample research method uses purposive sampling. The data analysis technique used is descriptive statistical analysis, multiple regression analysis, classical assumption test, t test (partial test), f test (simultaneous), and the coefficient of determination using the SPSS 21 program. The results of this study indicate that Profitability has a positive effect on firm value and Liquidity has a negative effect on firm value. Simultaneously that Profitability and Liquidity, have an effect on Company Value